2004
DOI: 10.1016/j.femsle.2004.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence for histidine kinase HP165 being an acid sensor of Helicobacter pylori

Abstract: Helicobacter pylori is a human gastric pathogen which is extremely well adapted to its unique habitat. Crucial for the survival under the acidic conditions prevailing in the stomach is the enzyme urease. Transcriptome analysis has shown that transcription of a large number of genes responds to the exposure of H. pylori to acid including the genes encoding the urease subunits UreA and UreB as well as several genes which have been previously identified as target genes of the two-component system HP166-HP165. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
82
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(92 citation statements)
references
References 43 publications
10
82
0
Order By: Relevance
“…Hpn-like is upregulated at pH 5.0 (compared to pH 7.0) by the two-component system ArsRS (HP166-HP165) (Bury-Mone et al 2004;Pflock et al 2004;Pflock et al 2006). Both Hpn and Hpn-like are activated in the presence of nickel by the nickel sensor NikR (Contreras et al 2003).The regulation studies thus far suggest that the Hpn proteins would be expressed at a time when nickel detoxification and/or nickel storage would be an advantage.…”
Section: Hpn and Hpn-like Proteinsmentioning
confidence: 99%
“…Hpn-like is upregulated at pH 5.0 (compared to pH 7.0) by the two-component system ArsRS (HP166-HP165) (Bury-Mone et al 2004;Pflock et al 2004;Pflock et al 2006). Both Hpn and Hpn-like are activated in the presence of nickel by the nickel sensor NikR (Contreras et al 2003).The regulation studies thus far suggest that the Hpn proteins would be expressed at a time when nickel detoxification and/or nickel storage would be an advantage.…”
Section: Hpn and Hpn-like Proteinsmentioning
confidence: 99%
“…ArsR has been shown to regulate expression of numerous genes and appears to have the ability to interact with the promoters of some genes in the non-phosphorylated form while interacting with others only when phosphorylated (126,127,171). Previous EMSA assays showed that ArsR directly binds to the oorDABC promoter region and that this reaction did not require ArsR phosphorylation (171).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, H. pylori has evolved mechanisms to survive severe acid shock and grow under moderately acidic conditions. One of the important mechanisms by which H. pylori responds to acidic pH involves regulation of gene expression through a two-component signal transduction system (12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Several recent studies reported that an H. pylori TCS, ArsSArsR (acid-responsive signaling sensor/response regulator), responds to acidic conditions (12)(13)(14)(15)(16)(17)(18)(19)(20). This TCS consists of the histidine kinase protein, ArsS, and the RR protein, ArsR.…”
mentioning
confidence: 99%
See 1 more Smart Citation